Volatile and refractory abundances of F‐ and G‐type stars1. Issue 1 (6th February 2013) - González Hernández, J.I.; Delgado‐Mena, E.; Sousa, S. G.; Israelian, G.; Santos, N.C.; Udry, S.
Abstract We present a detailed chemical abundance analysis of a sample of F‐ and G‐type stars. We investigate the possibility that the presence of terrestrial planets could affect the volatile‐to‐refractory abundance ratios. Stars with and without planets exhibit very similar abundance behaviours, either for solar twins or even when considering the whole sample of 95 solar analogs, 33 with and 62 without detected planets, in the metallicity range –0.3 < [Fe/H] < 0.5. After removing the Galactic chemical evolution effects, the small differences in the abundance patterns of stars with and without planets practically disappear and the mean volatile‐to‐refractory abundance ratios of the two samples are very close to solar values. If the depletion signature depends on the size of the convective zone, then stars hotter than the Sun should, in principle, show enhanced volatile‐to‐refractory abundance differences. Thus, we have also selected a sample of late F‐ and early G‐type main‐sequence stars with high‐quality spectra. We have in total 29 planet‐host stars and 32 stars without planets in the Teff range 5950–6400 K. We find very accurate Galactic chemical trends of these hotter stars that match those of solar analogs. Finally, we compare the abundance ratios of volatile and refractory elements versus the condensation temperature of this sample of main‐sequence stars hotter than the Sun with respect to those of solar analogs, paying special attention to those stars containing super‐Earth‐like planets. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)